Effect of cement based coatings on durability enhancement of GFRP-wrapped columns in marine environments. (15th April 2017) - Kashi, Amin; Ramezanianpour, Ali Akbar; Moodi, Faramarz
Highlights: This paper investigates the durability of GFRP sheets in tidal zone of marine environment. A marine simulator environment was designed and constructed similar to the real conditions. Ultimate strength and strain of confined specimens were affected after exposure. Polymeric and self-compacting mortar coatings can improve the durability of GFRP in marine environment. Abstract: The main objective of this paper is to study the effects of marine environments on cement based coatings for enhancing the durability of Glass Fibre Reinforced Polymer (GFRP) sheets. Despite of durability degradation in harsh environments, GFRP sheets are widely used to repair the existing structures in the marine environment. Mean while there is no comprehensive analysis has described how the environmental conditions affect these sheets, and there is no any appropriate solution has been provided to date. In this research, a marine environment simulator was designed and constructed similar to the real conditions. Mechanical properties of wrapped specimens were studied after placing them inside the simulator. Two types of cement based mortar, namely polymeric and self-compacted, were applied on the sheets. The polymeric mortar increased the ultimate strength of the specimens wrapped with one and two layers of GFRP by 5.4% and 4.7% respectively, compared with similar specimens in the marine environment without the protective mortar. The ultimate strength was increased by 2.4% and 1.8% in specimens with self-compacted mortar coatings. Marine environments caused better curing of the self-compacted mortar and conversely a slight reduction of polymeric mortar's durability. Also, the bond strength of the polymeric mortar to GFRP sheets was more than those with self-compacted mortar.